Adding HTML5 drag and drop to SharePoint Lists. Building HTML5 applications. IN Building HTML5 Applications. - Markeev, Andrey (MSDN magazine)
SharePoint doesn?t have any built-in HTML5 goodness, but don?t let that stop you. Andrey Markeev demonstrates how easy it is to add HTML5 drag-and-drop support to SharePoint?and why that?s just the beginning.